Wind erosion of soil influenced by clay amendment in the inland Pacific Northwest, USA. (13th August 2020) - Pi, Huawei; Huggins, David R.; Sharratt, Brenton
Abstract: Soil clay content is one of the primary intrinsic soil properties affecting soil erodibility and ecological processes, but few studies have tested the effects of clay amendment on wind erosion of soil. The objective of this study was therefore to evaluate the effect of progressive clay amendment on wind erosion of soil in the inland Pacific Northwest, where there is a high soil erodibility risk due to the arid and semiarid environment and sandy soils. Clay amendment significantly increased crust crushing energy when physical soil crusts formed after simulated rainfall. Crusts were then subject to simulated tillage to create an erodible soil surface before determining wind erosion in a wind tunnel. Soil loss significantly decreased with increasing clay amendment, even for low clay amendments (2%), soil loss at this percentage of clay amendment was 13.1–99.7% lower as compared with a soil surface devoid of clay amendment for the four soil types. The rate of change in erosion decreased with increasing amounts of clay amendment. Clay amendment was more effective in decreasing soil loss for two sandy loams or soil types with lower clay content. Clay amendment decreased soil loss primarily due to its impact on increasing aggregate geometric mean diameter (GMD), but aggregate crushing energy is also important in decreasing soil loss in terms of decreasing abrasion flux. Clay amendment is thus an effective way to restrain land deterioration in terms of increasing crust crushing energy, aggregate GMD, and decreasing abrasion flux.